HYPOTHALAMIC VASCULARIZATION IN THE GOATS AS REVEALED BY VASCULAR CORROSION CAST - A.A.sawad (Basrah Journal of Veterinary Research)
The heads ol‘ ten adult goats ol‘ both sexes were used to study the hypothalamic blood supply .lt was found that the hypothalamus is ‘supplied by branches of cranial cerebral , cranial communicating arteries, caudal communicating as well as from tiny branches of ophthalmic artery. The blood supply ol‘ mammillary body branches from the caudal cerebral, communicating and last branches ol‘ basilar artery. The hypothalamus is rather small in comparison to the rest of brain. Its blood supply is extremely rich , feeding from many branches ofcranial cerebral arteries that forms the circle ofwillis. This indicates that the hypothalamus has very high activity.